Prototype Sistem Pembagian Beras Bansos Berbasis IoT Menggunakan E-KTP - Marwan Ramdhany Edy; Rini Hairunnisa; Muhammad Fardan; Ainun Zahra Adistia (Sakura Publisher, 2023)
This study aims to design an IoT-based social assistance rice distribution system using e-KTP which can provide convenience in distributing rice to beneficiaries, practical and automatic social assistance only by bringing the e-KTP that has been registered without having to queue any longer. The results of the study show that the social assistance rice distribution system makes it easy for related village officials to distribute social assistance rice efficiently and effectively. The result of testing this system is that on each e-KTP there is a unique code that is different for each card which will be processed by the microcontroller and the data will be compared with the data registered in the database, with that if the user is registered the LCD will display a successful registered notification, but only Only e-KTPs that have been registered can collect this social assistance rice. Furthermore, there is a pin access on this tool as a second security which allows the recipient to be sick and can be represented by accessing it through the pin that has been inputted into the database.